Global Fossil Fuel Subsidies Remain Large : An Update Based on Country-Level Estimates - Coady, David (IMF Working Papers; Working Paper ;, 2019)
This paper updates estimates of fossil fuel subsidies, defined as fuel consumption times the gap between existing and efficient prices (i.e., prices warranted by supply costs, environmental costs, and revenue considerations), for 191 countries. Globally, subsidies remained large at USD 4.7 trillion (6.3 percent of global GDP) in 2015 and are projected at USD 5.2 trillion (6.5 percent of GDP) in 2017. The largest subsidizers in 2015 were China (USD 1.4 trillion), United States (USD 649 billion), Russia (USD 551 billion), European Union (USD 289 billion), and India (USD 209 billion). About three quarters of global subsidies are due to domestic factors-energy pricing reform thus remains largely in countries' own national interest-while coal and petroleum together account for 85 percent of global subsidies. Efficient fossil fuel pricing in 2015 would have lowered global carbon emissions by 28 percent and fossil fuel air pollution deaths by 46 percent, and increased government revenue by 3.8 percent of GDP.